2021
DOI: 10.3389/fmars.2021.768668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seagrass Wasting Disease on Eelgrass Growth and Belowground Sugar in Natural Meadows

Abstract: Seagrass meadows provide valuable ecosystem benefits but are at risk from disease. Eelgrass (Zostera marina) is a temperate species threatened by seagrass wasting disease (SWD), caused by the protist Labyrinthula zosterae. The pathogen is sensitive to warming ocean temperatures, prompting a need for greater understanding of the impacts on host health under climate change. Previous work demonstrates pathogen cultures grow faster under warmer laboratory conditions and documents positive correlations between warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Eelgrass also exhibits consistent relative growth rates of 1-2% per day globally, which means that longer leaves grow faster in absolute terms (Ruesink et al 2018), and the negative correlation between disease severity and blade area shown here and in prior work (Groner et al 2016(Groner et al , 2021 suggests that eelgrass leaves can outgrow lesions. However, in some cases, possibly when plants are stressed, lesion growth rate can outpace leaf growth (Graham et al 2021). Furthermore, the positive correlation of lesion area with temperature anomalies suggests that damage to plant tissues from wasting disease will increase with warming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eelgrass also exhibits consistent relative growth rates of 1-2% per day globally, which means that longer leaves grow faster in absolute terms (Ruesink et al 2018), and the negative correlation between disease severity and blade area shown here and in prior work (Groner et al 2016(Groner et al , 2021 suggests that eelgrass leaves can outgrow lesions. However, in some cases, possibly when plants are stressed, lesion growth rate can outpace leaf growth (Graham et al 2021). Furthermore, the positive correlation of lesion area with temperature anomalies suggests that damage to plant tissues from wasting disease will increase with warming.…”
Section: Discussionmentioning
confidence: 99%
“…Larger lesion areas will reduce photosynthetic capacity and can damage plant tissue that is not visually infected (Ralph and Short 2002). Infected plants also grow more slowly, and plants with more severe infections can accumulate less sugar in belowground tissues (Graham et al 2021). Many of the meadows surveyed here may therefore experience negative physiological impacts, with possible consequences for diminished ecosystem function.…”
Section: Discussionmentioning
confidence: 99%
“…The RNL pathway is also involved in stomatal closure (Chini et al ., 2004), so it may have been lost as part of the general loss of genes involved in stomatal pathways, as seagrasses do not have stomata. The two new genomes presented here will form the basis for future research into seagrass mechanisms of disease resistance and provide future opportunities to monitor diseases such as wasting disease, which is predicted to worsen with climate change (Graham et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass wasting disease, which is common in Zostera marina populations, is associated with the effects of environmental stressors including changes in sea surface salinity, temperatures, and ocean acidification [ 110 ]. The increased occurrence and severity of wasting disease outbreaks increase with salinity change, ocean warming, and light limitation [ 111 , 112 ]. A consequence of salinity and sea surface temperatures (SST) changes resulted in the release of high amounts of hydrogen peroxide (H 2 O 2 ) by K. alvarezii , which may have increased its vulnerability to disease [ 57 ].…”
Section: The Emergence Of Seaweed Diseases and Prevalent Threats To S...mentioning
confidence: 99%